Bureaucratic Accountability In The Management of The Operational Fund School (BOS) (Case Study On Elementary Education Kupang) - Marini Sari Dewi Seger (MAMEN: Jurnal Manajemen, 2022)
The Government in a democracy should be accountable to the public because the public authority as the holder of the key. The Government should be more transparent and responsible in managing resources public funds or a public authority. Bureaucratic accountability carried out in a balanced  internal and external way so that it can produce the performance of education bureaucrats in accordance with the rules and give a sense of smug for stakeholders in the education system. The research aims to find out the school internally and externally bureaucracy Accountability, the control between bureaucratic accountability in the school and methods can ensure the accountability of the school bureaucracy. This type of research uses the instrumental case studies to examine a case in order to be presented a perspective on the issue or theory. The data collected with qualitative methods, documents, archive footage, interviews, direct observation, as well as the role of observation, and physical devices. The informant set by purposive. Data validation using triangulation technique. Research results generate internal accountability carried out by the school. Management of the Fund BOS does not match the technical rules but the school's responsibility to accept the consequences of their performance. While the external accountability is not implemented by the school. The school did not involve the stakeholders of the school Committee, teachers and parents in the process of management of the Fund BOS, does not make use of the media the school as school accountability to the public as well as the use of funds of the BOS is not in accordance with the needs of the stakeholders. An imbalance of internal and external accountability requires a control method to ensure the accountability of public control that is supporting the implementation of the control hierarchy, professional, legal, and political.